Aktivitas nokturnal Aedes (stegomyia) aegypti dan Aedes (stegomyia) albopictus di berbagai daerah di Kalimantan - Muhammad Rasyid Ridha; Abdullah Fadilly; Nur Afrida Rosvita (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2017)
Dengue and chikungunya are increasing global public health concerns due to their rapid geographical spread and increasing disease burden. Knowledge of the activity of sucking blood at night (nocturnal) Ae. aegypti and Ae. albopictus in some areas of Borneo need to be known. Natural population of Aedes was collected by human bait collection and resting collection from 18:00 to 06:00 out door and indoor. The biting activities of Ae. aegypti and Ae. albopictus occurred throughout the night from 18:00 to 05:50 out door and indoor in Dadahup and Mandomai, Kapuas District, Central Kalimantan (2015), Pulau Ku’u, Tabalong district, South Kalimantan (2011), Bangkal Ulu, Kutai Timur district, East Kalimantan (2012), and Antaraya and Karyajadi, Barito Kuala district, South Kalimantan (2016). These results showed that the biting activities of Ae. aegypti dan Ae. albopictus did not only occur diurnally but also nocturnally.